Menghadapi Dampak Psikis dari Media Sosial di Era Society 5.0 - Mohammad Fajar Rifqi; Aji Wibawa (Universitas Ngeri Malang, 2023)
Social media has become an integral part of modern society, and its impact on individuals has been a topic of increasing interest in the age of Society 5.0. Through a comprehensive review of literature, it was found that social media has both positive and negative impacts on individuals, depending on various factors such as frequency of use, content consumption, and social comparison. The positive effects of social media include providing individuals with a sense of connection and social support, especially during times of social isolation. However, excessive use of social media can lead to negative outcomes such as increased anxiety, depression, and social comparison. It is recommended for social media platforms to implement policies and features that can protect users from harmful content and facilitate positive interactions. The findings suggest the importance of being mindful of social media use and promoting positive digital environments. Further research is needed to explore the long-term effects of social media use and to identify effective interventions to address its negative impact. Media sosial telah menjadi bagian yang tidak terpisahkan dari masyarakat modern, dan dampaknya terhadap individu telah menjadi topik yang semakin menarik di era Masyarakat 5.0. Melalui tinjauan pustaka yang komprehensif, ditemukan bahwa media sosial memiliki dampak positif dan negatif terhadap individu, tergantung pada berbagai faktor seperti frekuensi penggunaan, konsumsi konten, dan perbandingan sosial. Efek positif dari media sosial termasuk memberikan individu rasa terhubung dan dukungan sosial, terutama selama masa isolasi sosial. Namun, penggunaan media sosial yang berlebihan dapat menyebabkan hasil negatif seperti peningkatan kecemasan, depresi, dan perbandingan sosial. Platform media sosial disarankan untuk menerapkan kebijakan dan fitur yang dapat melindungi pengguna dari konten berbahaya dan memfasilitasi interaksi yang positif. Temuan ini menunjukkan pentingnya untuk berhati-hati dalam menggunakan media sosial dan mempromosikan lingkungan digital yang positif. Penelitian lebih lanjut diperlukan untuk mengeksplorasi efek jangka panjang dari penggunaan media sosial dan untuk mengidentifikasi intervensi yang efektif untuk mengatasi dampak negatifnya.